BILANGAN PEROKSIDA MINYAK GORENG CURAH DAN SIFAT ORGANOLEPTIK TEMPE PADA PENGULANGAN PENGGORENGAN - Siti Aminah . (Universitas Muhammadiyah Semarang, 2010)
The reactions that occur during the frying oil will damage the stability and the fried ingredients. The objective of research in general is to determine the effect of frying on the number of repeated frying to peroxide value, organoleptic characteristic of tempe and cooking oil. Design research using Complete Random Design (CRD) 2 repetition one factor that is repeated frying (1, 5, 10, 15, and 20). Variable in this research is bulk cooking oil and tempe. Chemical analysis consisted of the determination of water content of tempe (oven method) and the number of bulk cooking oil peroxides (AOCS Cd 8-53). The Data are then analyzed using Analysis of Variance (ANAVA) with further test LSD (Least Significant Difference). The more repeated frying peroxide number is increasing. Color and aroma becomes less good tempe and cooking oil with repeated frying. Keywords: peroxide number, organoleptic characteristic, bulk cooking oil